Percutaneous Transluminal Mitral Commissurotomy using Inoue Balloon in Iraqi population - Bairam, Amjad R.; Al-Kinani, Tahseen; Al-Kuraishi, Muthanna; Abdul Ameer Mohammed, Ali-; Zahra Flaih Hussain, Abdul (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Mitral stenosis (MS) is the most common valve disease in developing countries and there are many ways to deal with this condition. The aim of this study was to evaluate the immediate results of percutaneous transvenous mitral commissurotomy (PTMC) in patients with severe symptomatic rheumatic mitral stenosis.Patients and Methods: From May 2006 to August 2007, 58 patients (17 male, 41 female) with age range (16-57) years, underwent PTMC in Ibn AL- Bitar Hospital for Cardiac Surgery. All the patients were symptomatic, their MVA 1.5 cm2 with NYHA class II-IV. Clinical evaluation and echocardiographic examination were carried out before and after PTMC, mitral valve structures were assessed using Wilkins score. The procedure was performed under local anesthesia, using the step-wise Inoue balloon technique with the antegrade transvenous approach.Results: The procedure was successful in 51(88%) of the patients and unsuccessful in the remaining 7(12%) patients. Successful result was defined as post procedure mitral valve area ( MVA) 1.5 cm² as assessed by echocardiography and no mitral regurgitation (MR)>2 according to sellers classification. Mitral valve area increased from 0.93 ±0.2 to 1.84±0.2 cm² after the procedure (P